Pelatihan modifikasi model pembelajaran bagi guru SD se-Kecamatan Kahu - A.M. Irfan Taufan Asfar; A.M. Iqbal Akbar Asfar; Cheriani Cheriani (Universitas Negeri Makassar, 2020)
This community partnership program (PPM) aims to improve teacher professionalism through modification of the learning model. Improving learning practices is an alternative for the development of quality of learning that is oriented towards the benefit of students. The method used in community partnership activities with resembles a ToT (trainer of trainer) form by collaborative-participatory dialogic approach includes in-house training (lectures, questions and answers, discussions) for the delivery of material, direct practice for making modifications to learning models, testing, modeling modification practices. Supervision and visits to ensure the running of training results and to get support from resources in the continued implementation of improving the quality of learning. The training participants in the community partnership program activities included 15 participants from several elementary school teachers in Kahu Subdistrict and also involved students as teacher assistants in modifying the learning model. The results achieved are knowledge partners about learning models, partners are able to modify learning models according to teaching materials and class situations that are innovative, interesting and fun.